Allais for the poor: Relations to ability, information processing and risk attitudes - Tabea Herrmann; Olaf Hübler; Lukas Menkhoff; Ulrich Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper complements evidence on the Allais paradox from advanced countries and educated people by a novel investigation in a poor rural area. The share of Allais-type behavior is indeed high and related to characteristics of "lacking ability", such as poor education, unemployment, and little financial sophistication. Based on prospective reference theory, we extend these characteristics by biased processing of probabilistic information. Finally, we reveal that Allais-type behavior is linked to risk-related characteristics, such as risk tolerance and optimism. This indicates a potential problem as exactly the more dynamic among the poor tend to make inconsistent decisions under uncertainty.
Keywords: D81; D03; O10; 330; field experiments; Allais paradox; socio-demographic characteristics; prospective reference theory; first order stochastic dominance; risk attitude; optimism